Manajemen Risiko Penyaluran Donasi Infaq dan Sedekah Ke Palestina pada Lembaga Kemanusiaan Mer-C Indonesia: Medical Emergency Rescue Committee - Magfuroh, Abdah; Suryaman, Maman (Ikatan Da'i Indonesia, 2024)
Donation or donation is a voluntary element and does not expect a return of service or voluntary reward to have a noble value. It’s more of a human or human interest. A gift that is generally material or non-material. This study discusses the risk management of the distribution of donations to Palestine at the humanitarian agency MER-C Indonesia. This research was carried out with the aim of finding out the process of donation distribution and risk management of the distribution of donations to Palestine by MER-C Indonesia. Djohanputro defines risk management as a structured and systematic process in identifying, measuring, mapping, developing alternative risk management and monitoring and controlling risk management implementation. (2019:112) The type of research used is a descriptive qualitative approach. The data used in this study are primary data in the form of interviews with staff or employees of MER-C Indonesia and secondary data of scientific journals. Data collection using triangulation techniques; i.e. observations, interviews and documentation. Further data processing techniques used in this research include editing, organizing and discovery of results. As for the results of the research, donations were distributed to Palestine through two programmes, the Indonesian Hospital in Gaza development program and the humanitarian aid program. Moreover, risk management of donation distribution is carried out MER-C by sending Indonesian volunteers to Palestine, making Egypt an alternative in channeling essential aid from outside the Palestinian territory, cooperating with various media partners and constantly updating through social media in the distribution of donations to Gaza, Palestine.